Evaluation of Different Types and Amounts of Amendments on Soil Cd Immobilization and its Uptake to Wheat - Zhou, Changrui; Yuan, Haiyan; Ning, Chuanchuan; Li, Shuailin; Xia, Zhuqing; Zhu, Mengmeng; Ma, Qiang; Yu, Wantai (Environmental management (New York), 2020)
Using amendments is a cost-effective method to soil cadmium (Cd) remediation, whereas knowledge about how different amendments and rates affect remediation efficiency remains limited. This study aimed to evaluate the impacts of different types and amounts of amendments on soil Cd immobilization and its uptake by plants. Biochar (BC), zeolite (ZE), humic acid (HA), superphosphate (SP), lime (L), and sodium sulfide (SS) were applied at three rates (low, medium, and high) ranging from 0.5 to 5%. The concentration of CaCl 2 -extractable Cd was considerably affected by the amendments, except HA, and the high doses achieved better immobilization effects than the low doses did. The addition of amendments decreased weak acid soluble Cd by 4.1–44.0% but slightly increased the fractions of oxidizable and residual Cd. These amendments (except BC and HA dose of 1%) decreased Cd accumulation in grains by 1.3–68.8% and (except SP) in roots by 16.3–65.5% compared with the control. The SP efficiently immobilized Cd but posed a potential soil acidification risk. Moreover, SS treatment increased the soil electrical conductivity (EC) value and restricted the growth of wheat, possibly due to high-salt stress. BC, ZE, and L exerted significant effects on the reduction in available Cd as the application rate increased. These amendments enhanced Cd immobilization mainly by changing Cd availability in soil and influencing its redistribution in different fractions in soil and root uptake by plants. This study concluded that BC-5%, ZE-1%, and L-0.5% can be used for Cd immobilization in acidic or neutral soils.